Fabrication of chitosan/polyvinyl alcohol/amine modified carbon nanotube composite films for rapid chromate removal - AYDIN, YAŞAR ANDELİB (WILEY, 2021)
Composite adsorbent films with amine and hydroxyl functionalities were synthesized from chitosan (CS), polyvinyl alcohol (PVA), and amine-modified carbon nanotubes (a-MWCNT) by solvent casting method. Weight proportions of CS to PVA and weight percent of a-MWCNT were optimized to achieve highest chromate removal capacity. Structural characteristics of the composites were investigated using scanning electron microscopy, Fourier transform infrared spectroscopy, Raman spectroscopy, and thermal gravimetric analysis. Accordingly, incorporation of a-MWCNT to CS/PVA structure resulted in the generation of nanochannels, which enhanced adsorption capacity. Moreover, the composite comprising 0.4% wt. a-MWCNT provided over 99% of Cr (VI) removal from 50 mg L-1 Cr (VI) solution within five minutes of contact time. Redlich-Peterson and Radke-Prausnitz isotherm models provided the highest conformity to adsorption data. Maximum chromate sorption capacity of CS/PVA/a-MWCNT composite film was determined as 134.2 mg g(-1) being 172% higher than that of CS/PVA. Regeneration was best achieved in 1.0 M NaOH and the composite was shown to retain at least 70% of its original capacity after five consecutive adsorption-desorption cycles.
Keywords: biopolymers and renewable polymers; composites; nanotubes; graphene and fullerenes; adsorption; kinetics; HEAVY-METAL IONS; AQUEOUS-SOLUTION; POLY(VINYL ALCOHOL); WASTE-WATER; COPPER IONS; ADSORPTION; MEMBRANES; CHROMIUM; CHITOSAN; SORPTION